هوامش في الجانب الفكري للسرد المقدس - الساعدي رحيم محمد سالم (Al-Adab Journal, 2019)
The Holy narrative dazzle our imagination, and as we moved away from talking about the nature of the sacred narratives and the branches of that essence, it is necessary to uncover the intellectual elements of that narration, or to interpret the text to extract its truth and fertility. But what can we know from the features of the narrative and the sacred text that sometimes frightens us or restricts the rules of our ideas to extract new or different? In the study try to address the aspects that represent the idea contained in the story, and talk about the Quranic stories indicates that the Koran book can provide different or new and we can understand and discover the new variant and belonging to the modernist side of the Koran. And look at the surrounding narrative of the Koran, will lead us to: 1-Imagination 2 - brainstorming 3 - Inductive approach 4 - the use and employment of science 5 - re - refining images and merge them with each other 6 - application of ideas - Conclusion. The investment of the sacred narrative in the Qur’an will mean that we are trying to operate our intellectual tools to build the different intellectual aspects in any narration and then to know the links that relate to the human sciences and their relations and to benefit from them in reading the intellectual and the physical scene. In the Koran or the Torah or related stories will mean the relationship and impact of that story on the world literature and science and the ideological side ... etc. Thus, we can use the narratives of narration in the production of the curriculum or thought or wisdom, which are not absent from the ideas of specialists in the Koranic studies or critics of the sacred text. I believe that the compatibility of the intellectual with the narrative aspect of the sacred texts - especially in the Koran - represents the salvation of the Koran from the dogmatic perception that restricts the science of the Koran and transmits it to a code that does not produce coherent thought and dispel scientific, methodological or organizational bases. Here I wanted to define intellectual windows or The map that goes into understanding and building narrative.